The Myth Of Masculinity And The Construction Of The Father's Role In The Kapal Api Advertisement 'Semangat 100% Seorang Ayah': A Semiotic Analysis By Roland Barthes - Azizah, Rahmalia Wulan; Hikmah, Nurul (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to reveal how the myth of masculinity and the construction of the father's role are represented in Kapal Api's advertisement entitled “Semangat 100% Seorang Ayah” (100% Spirit of a Father). This study uses Roland Barthes' semiotic approach, tracing the meanings formed through visual, verbal, and narrative signs that appear in the advertisement. Data was obtained through literature study and analysis of several images from advertisements uploaded on Kapal Api's official YouTube channel, focusing on symbols that highlight the relationship between masculinity, work, and sacrifice. The results show that the advertisement constructs the image of a father as a hard-working, tough, and responsible figure. This is an ideal image of masculinity that has long existed in Indonesian culture. Coffee serves as a symbol of energy, determination, and zest for life that reinforces patriarchal values of men as the main breadwinners of the family. However, this advertisement also reveals a new layer of meaning by presenting the figure of a warm, loving father who is close to his family. This marks a shift in the representation of masculinity towards a more empathetic and humanistic portrayal. Thus, the Kapal Api advertisement not only reproduces the old myth of men as dominant figures, but also presents a narrative of balance between strength and gentleness. Through strong visual and symbolic strategies, this study confirms that advertisements are an important medium in shaping and negotiating social meanings about the role of fathers and masculine identity amid changes in modern Indonesian cultural values.